Acessando convergência evolutiva no registro fóssil: morfologia e biomecânica de Proterochampsa nodosa Barberena 1982 (Archosauriformes: Proterochampsidae) e sua relação com os crocodiliformes - Oliveira, Daniel de Simão (2023)
Proterochampsidae is an extinct group of medium-sized predators endemic to South America, with its fossil record restricted to Triassic continental deposits in Brazil and Argentina. Due to their superficial resemblance to animals such as alligators and crocodiles, these creatures have historically been interpreted as semi-aquatic predators, believed to have had a similar lifestyle and feeding niche to the ecological role occupied by crocodilians today. However, there is still a scarcity of studies that rigorously test these inferences concerning the group. Facing this challenge, the aim of this thesis is to assess evolutionary convergence and functional morphology in proterochampsids through morphological and biomechanical studies, focusing on the Brazilian proterochampsid Proterochampsa nodosa. The first part of the thesis, in addition to the osteological study and anatomical redescriptions of P. nodosa, focuses on the taxonomy of P. nodosa and anatomical comparisons with its sister species from Argentina, P. barrionuevoi. A detailed description of the anatomy of P. nodosa has improved the taxon's diagnosis and clarified the distinctions between the two Proterochampsa species, reinforcing the taxonomic validity of these taxa. Regarding the behavior and feeding mechanics of P. nodosa, investigated in the second part of the study, it appears that Proterochampsa would have been capable of developing a predation pattern similar to that of gharials and false gharials, as inferrerd by the similar distribution of stresses on the long mandibles, especially when subjected to the anterior biting simulation. The biomechanical study compared the jaw mechanics of Proterochampsa with that of Alligator mississippiensis (the American alligator) and Tomistoma schlegelii (the false gharial). Finite element analysis indicates that Proterochampsa would have had a bite force capability comparable to that of Alligator mississippiensis, although subject to higher bending stresses. Furthermore, the study of adductor musculature revealed that, despite differences in muscle conformation, Proterochampsa would have had the ability to achieve comparable results, albeit through different means. In conclusion, it was observed that while this muscular arrangement allowed the extinct taxon to exhibit behaviors analogous to those of extant forms, the impact and distribution of stresses resulting from these habits were considerably more pronounced.